Growth Abnormalities in Children with Chronic Hepatitis B or C. (4th March 2012) - Gerner, P.; Hörning, Andre; Kathemann, S.; Willuweit, K.; Wirth, S.
Abstract : Background . It has been suggested that chronic hepatitis B infection leads to growth impairment, but data are inconsistent and underlying factors are not defined. Methods . Children and adolescents with chronic hepatitis B (HBV) or C (HCV) were retrospectively evaluated for growth, weight, antiviral treatment, biochemical signs of liver inflammation, route of infection, and HBV DNA, respectively. Results . In all, 135 children (mean age 6.1 years, 81 male, 54 female) with HBV (n = 78 ) or HCV (n = 57 ) were studied. Route of infection was vertical in 50%, parenteral in 11%, and unknown in 39%. ALT levels were above 1.5 times above normal in 30% while 70% had normal/near normal transaminases. 80% were Caucasian, 14% Asian, 1% black, and 4% unknown. Mean baseline height measured in SDS was significantly lower in the study population than in noninfected children (boys −1.2, girls −0.4, P < 0.01 ). 28 children were below 2 standard deviations of the norm while 5 were above 2 standard deviations. SDS measures in relation to individual factors were as follows: elevated ALT: boys −1.4, females −0.5 (P < 0.01 ), ALT normal/near normal: boys +0.4, females +0.6; parenteral transmission: boys −3.3, girls −0.9 (P < 0.01 ), vertical transmission: boys −0.2, females −0.2. Antiviral treatment itself or HBV-DNA load did not reach statistically significant differences. Conclusions . Chronic HBV or HCV may lead to compromised growth which is mostly influenced by liver inflammation. Our data may argue for early antiviral treatment in children with significant ALT elevation.